Pengaruh Kompensasi dan Budaya Organisasi terhadap Loyalitas Karyawan Coca-Cola Official Distributor Bandung - Kervin Nazar Pamungkas; Allya Roosallyn Assyofa; Aditia Wirayudha (Bandung Conference Series: Business and Management, 2024)
Abstract. Coca-Cola Official Distribution Bandung is one of the official Coca-Cola product distribution companies in Bandung that distributes these products. Coca-Cola Official Distributor Bandung always strives to improve the welfare of its employees by implementing appropriate compensation. Apart from that, the company strives to create a comfortable organizational culture, the family value felt by employees is quite high so that many people work there for a long time. To achieve this goal, Coca-Cola Official Distribution employees must have high loyalty which is supported, among other things, by compensation and organizational culture in the company. Based on this phenomenon, the problem in this research is formulated as follows: (1) How is compensation implemented at Coca-Cola Official Distribution Bandung? (2) What is the organizational culture at Coca-Cola Official Distribution Bandung? (3) How is employee loyalty at Coca-Cola Official Distribution Bandung? (4) How big is the influence of compensation on employee loyalty at Coca-Cola Official Distributor Bandung? (5) How much influence does organizational culture have on employee loyalty at Coca-Cola Official Distribution Bandung? (6) How big is the influence of compensation and organizational culture on employee loyalty at Coca-Cola Official Distribution Bandung? Researchers used an active quantitative approach method. The population selected in this research were all employees of the Coca-Cola Official Distribution Bandung, totaling 60 employees. Using a non-probability sampling technique with a saturated sampling method which took the entire population as research respondents, a total research sample of 60 employees was obtained. The data collection techniques used in this research were questionnaires, interviews, observation and literature study. The data analysis technique used in this research is descriptive analysis technique. The results of this research are: There is a positive and significant influence between compensation on employee loyalty at Coca-Cola Official Distribution Bandung which is in the weak category, there is a positive and significant influence between organizational culture on employee loyalty at Coca-Cola Official Distributor Bandung in the weak category and also Based on simultaneous hypothesis testing, the Compensation variable and the Organizational Culture variable have a positive and significant effect together (simultaneously) on the Employee Loyalty variable which is in the very weak category. Abstrak. Coca-Cola Official Distributor Bandung selalu berupaya dalam mensejahterakan karyawanya dengan penerapan kompensasi yang sesuai. Selain itu perusahaan tersebut berupaya dalam menciptakan budaya organisasi yang nyaman, nilai kekeluargaan dirasakan oleh karyawan cukup tinggi sehingga banyak sekali yang bekerja disana dengan waktu yang lama. Untuk mencapai tujuan tersebut para karyawan Coca-Cola Official Distributor harus memiliki loyalitas tinggi yang didukung salah satunya oleh kompensasi dan budaya organisasi yang ada di perusahaan Peneliti menggunakan metode pendekatan kuantitatif verikfiaktif. Populasi yang dipilih dalam penelitian ini adalah seluruh karyawan Coca-Cola Official Distributor Bandung yang berjumlah 60 karyawan. Dengan teknik pengambilan sampel non probability sampling dengan metode sampling jenuh yang mengambil seluruh populasi sebagai responden penelitian diperoleh jumlah sampel penelitian sebanyak 60 karyawan. Teknik pengumpulan data yang digunakan dalam penelitian ini adalah kuesioner, wawancara, observasi, dan studi pustaka. Adapun teknik analisis data yang digunakan dalam penelitian ini adalah teknis analisis deskriptif. Hasil dari penelitian ini adalah: Terdapat pengaruh positif dan signifikan antara kompensasi terhadap loyalitas karyawan di Coca-Cola Official Distributor Bandung yang termasuk kategori lemah, terdapat pegaruh positif dan signifikan antara budaya organisasi terhadap loyalitas karyawan di Coca-Cola Official Distributor Bandung kategori lemah dan juga berdasarkan uji hipotesis secara simultan, variabel Kompensasi dan variabel Budaya Organisasi berpengaruh positif dan signifikan secara berama-sama (simultan) terhadap variabel Loyalitas Karyawan yang termasuk kategori sangat lemah.